Rohingya Refugees in Malaysia: Rhetoric vs Reality / Shimaa Shazana Mohd Ali ... [et al.] - Mohd Ali, Shimaa Shazana; Ahmad, Yarina; Tahir, Nor Suziwana; Ayob, Nor Azira (2021)
The issue of Rohingya refugees is not new in Malaysia. It has existed since the end of the 1970s and escalated by the 1980s (Kassim, 2015; Letchamanan, 2013). However, some scholars argue that their first arrival was in the late 1990s (Palik, 2020). Despite many measures undertaken by the Malaysian government to strengthen border security and enforcement, statistics of Rohingya refugees continue to increase (UNHCR, 2021). Based on the latest record from UNHCR in Malaysia, it is estimated around 178,450 refugees and asylum seekers are registered. It comprises 153,800 Myanmar, dominate by Rohingyas (102,020), Chins (22,440), and other ethnicities (29,340). While many debates are surrounding the Rohingya refugees’ issue, this paper argues the rhetoric and reality of this issue in the Malaysian context. The discussion of this paper is based on reviewing relevant literature in Malaysia, as well as in other countries.